Assessment of block and random copolymer overlayers on polymer optical fibers toward protein detection through electrostatic interaction. Issue 5 (21st November 2014) - El Sachat, Alexandros; Meristoudi, Anastasia; Pispas, Stergios; Riziotis, Christos
ABSTRACT A simple fiber optic based scheme for the selective detection of proteins, based on surface electrostatic interactions, is presented. The implementation of this method is conducted using a modified polymer optical fiber's surface and thin overlayers of properly designed sensitive copolymer materials with predesigned molecular characteristics. Block poly(styrene‐b‐2vinylpyridine) (PS‐b‐P2VP) and random PS‐r‐P2VP copolymers of the same monomers and similar molecular weights, were modified and used as sensing materials. This configuration proved to be efficient concerning the fast detection of charged proteins, and also the efficient discrimination of differently charged proteins such as lysozyme and bovine serum albumin. Results on the sensing performance of block and random copolymers are also discussed drawing conclusion on their efficiency given their considerable different fabrication cost. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 327–334